The Implementation of ISO 9001:2015 in Drainage Project Execution Based on Failure Mode and Effect Analysis (FMEA) - Mira Wikoyati; Endah Kurniyaningrum (Pandawan Sejahtera Indonesia, 2026)
Urban drainage projects play a strategic role in controlling runoff and mitigating flooding. However, construction quality issues often arise during implementation, leading to channel failure. This study aims to analyze the impact of implementing the ISO 9001:2015 Quality Management System on the quality of drainage projects using the Failure Mode and Effect Analysis (FMEA) approach, through a case study of the Rasuna Said drainage channel in Kuningan, Jakarta. The research methodology combines primary and secondary data obtained through field observations, interviews, questionnaires based on ISO 9001:2015 clauses, and project document analysis. Quality risk identification is conducted using the FMEA method, with severity, occurrence, and detectability parameters assessed to determine the Risk Priority Number (RPN). The results show that the main failure modes with the highest risk levels include mismatched channel elevation and slope, loosely fitting channel element connections, uneven subgrade compaction, and initial sedimentation due to weak work environment controls. These risks are generally related to the field operational stage and the suboptimal application of the risk based thinking principle in ISO 9001:2015. The integration of the FMEA method with ISO 9001:2015 has been proven to identify and prioritize quality risks more systematically and support the development of measurable mitigation actions. This study concludes that the implementation of ISO 9001:2015, integrated with FMEA, can improve the effectiveness of quality control, minimize the risk of construction failure, and support the sustainability of urban drainage projects.